(untitled) (Annals of Medical Research, 2025)
Aim: Birth asphyxia and intrapartum brain injury can cause death or irreversible brain damage. The only known treatment that improves prognosis is therapeutic hypothermia. Our goal was to assess the parameters associated with death in newborns receiving therapeutic hypothermia. Materials and Methods: This retrospective cohort study was conducted in a neonatal intensive care unit (NICU) and included neonates who underwent therapeutic hypothermia due to perinatal asphyxia over 10 years. Patients were categorized into survivors and nonsurvivors based on their in-hospital outcomes. Demographic characteristics, clinical parameters, laboratory findings, and complications were retrieved from the patients’ medical records. Prognostic factors were compared between groups using appropriate statistical methods, and multivariate logistic regression was performed to identify independent predictors of mortality. Results: A total of 114 newborns treated with therapeutic hypothermia were analyzed, of whom 11 (9.6%) died due to perinatal asphyxia (PA). Non-survivors had significantly lower gestational ages (37±2 vs. 38.4±1.6 weeks, p=0.042), lower 5-minute Apgar scores (5 [1–5] vs. 5.5 [4–7], p=0.048), and higher cesarean delivery rates (81.8% vs. 41.7%, p=0.011). Severe findings on aEEG and Sarnat Stage III were more common among nonsurvivors (p<0.001 for both). Non-survivors also exhibited significantly lower admission rectal temperatures [33.8°C (32–36) vs. 35.8°C (34.5–36), p=0.023], higher rates of thrombocytopenia (81.8% vs. 42.7%, p=0.013), acute renal failure (90.9% vs. 39.8%, p=0.001), and cranial ultrasound abnormalities (27.3% vs. 3.9%, p=0.019). In the multivariate logistic regression analysis, only a lower rectal temperature at admission remained an independent predictor of mortality (OR: 1.520, 95% CI: 1.061–2.178, p = 0.023). Conclusion: Factors such as lower Apgar scores, acute renal failure, and hypothermia severity on admission are strongly associated with mortality. The early identification and management of these risk factors are critical for improving outcomes in neonates treated with therapeutic hypothermia.